2018
DOI: 10.1186/s40729-018-0145-3
|View full text |Cite
|
Sign up to set email alerts
|

Implant success and survival rates in daily dental practice: 5-year results of a non-interventional study using CAMLOG SCREW-LINE implants with or without platform-switching abutments

Abstract: BackgroundThe performance of dental implants in controlled clinical studies is often investigated in homogenous populations. Observational studies are necessary to evaluate the outcome of implant restorations placed in real-life situations, according to standard practice, and to assess the needs of the patients. The aim of this non-interventional study was to reveal the survival, success, and general performance of CAMLOG SCREW-LINE implants and their restorations in daily dental practice.MethodsSeventeen priv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 23 publications
6
27
0
3
Order By: Relevance
“…At the one-year follow-up, the survival and success rates were 96.15% and 94.62%, respectively. These data are similar to survival features reported otherwise in the literature [ 20 , 21 , 22 ]. More specifically, they compare well to a one-year study [ 23 ] dealing with 117 C1 implants placed in 60 patients by 7 experienced periodontists; the reported survival and success rates of these active private practice practitioners were 98.3% and 95.4% respectively.…”
Section: Discussionsupporting
confidence: 90%
“…At the one-year follow-up, the survival and success rates were 96.15% and 94.62%, respectively. These data are similar to survival features reported otherwise in the literature [ 20 , 21 , 22 ]. More specifically, they compare well to a one-year study [ 23 ] dealing with 117 C1 implants placed in 60 patients by 7 experienced periodontists; the reported survival and success rates of these active private practice practitioners were 98.3% and 95.4% respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Cacaci et al [ 31 ], found a survival rate of 98.4% at 36 months. and Beschnidt et al [ 32 ], in 2018, found cumulative survival rates of 100% at 1-year follow-up, 99.6% at 3-year follow-up and 98.6% at 5-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Prosthetic dental implant therapy for the replacement of missing teeth is a well-established treatment for the rehabilitation of partially or completely edentulous patients (Beschnidt et al, 2018;Schropp, Wenzel, & Stavropoulos, 2014). Despite the evidence of excellent long-term results, successful osseointegration is still a critical factor for dental implant rehabilitation, mainly in clinically challenging conditions (Benic et al, 2019;Deng et al, 2010;van Steenberghe, Jacobs, Desnyder, Maffei, & Quirynen, 2002).…”
Section: Introductionmentioning
confidence: 99%